(11aS)-7-Bromo-2,3,5,10,11,11a-hexahydro-1H-pyrrolo[2,1-c][1,4]benzodiazepine-3,11-dione - Ma, Chao (International Union of Crystallography, 2011)
The title compound, C(12)H(11)BrN(2)O(2), was prepared by an intra-cyclization reaction of (S)-1-(5-bromo-2-nitrobenzyl)-5-oxopyrrolidine-2-carboxylic acid methyl ester in the presence of EtOH/Fe. The five-membered pyrrolidinone ring adopts an approximate envelope conformation, while the seven-membered diazepanone ring displays a twisted boat conformation. Intermolecular classical N—H⋯O hydrogen bonds and weak C—H⋯O interactions help to stabilize the crystal structure.